Business Analytics: Synergy of Technology, Data and Strategic Thinking - Starchenko, Grygoriy; Iglesias-Sánchez, Patricia Pilar (Universidad de Málaga, 2024)
The section is dedicated to exploring the role of business analytics in the modern context of digital transformation and its impact on organizational management efficiency. It reveals the key idea of the synergy of technology, data, and strategic thinking as a triune mechanism for achieving sustainable development and business competitiveness. Technology provides tools for processing and analyzing large volumes of data, data serves as the foundation for informed decision-making, and strategic thinking directs these resources toward achieving long-term goals. Special attention is given to building a model of interaction between these three components, where technological potential enhances the speed and efficiency of data processing, and quality analytics ensures the accuracy of forecasts and strategic decisions. Strategic thinking, in turn, ensures the integration of analytical results into the organization’s overall strategy. The section also emphasizes the need for implementing analytical tools and fostering a data-oriented corporate culture. The authors highlight the importance of continuous staff training, integrating technological innovations, and adapting business processes to rapidly changing market conditions. In conclusion, the study demonstrates that the synergy of technology, data, and strategic thinking is a key factor for the successful transformation of businesses in the digital age and ensuring their sustainable development.
Colaboración con profesores de Universidades de Ukrania
Keywords: Empresas - Gestión; Business analytics; Data; Strategic thinking